The temporal dynamics of metacognitive experiences track rational adaptations in task performance - Luc Vermeylen; Senne Braem; Ivan I. Ivanchei; Kobe Desender; J. M. García-Román; Carlos González-García; María Ruz; Wim Notebaert (Communications Psychology)
Abstract Human task performance elicits diverse subjective metacognitive experiences, such as boredom, effort, fatigue, and frustration, which are considered to play important roles in the monitoring and regulation of cognitive processes. Yet, their specific contributions to task performance remain poorly understood. Therefore, we investigated the temporal dynamics underlying these metacognitive experiences and latent cognitive processes supporting task performance. We used a time-on-task design using a conflict task and analyzed the data using a comprehensive approach encompassing behavioral, model-based, subjective, and neural measures (N = 111). Our results show that changes in cognitive processes can be understood as a rational attempt to optimize task performance and that distinct metacognitive experiences are related to different aspects of this rational endeavor. These findings suggest that metacognitive experiences act as tools for humans to gain insights into the optimality of their cognitive performance.